Saloplastic membranes as green devices for soft tissue regeneration - Costa, Rui R. (2015)
Implantable devices must exhibit mechanical properties similar to native tissues to promote appropriate cellular behavior and regeneration. Herein, we report a new membrane manufacture method based on the synthesis of polyelectrolyte complexes (PECs) that exhibit saloplasticity, i.e. variable physical-chemistry using salt as a plasticizer. This is a Green Chemistry approach, as PECs generate structures that are stabilized solely by reversible electrostatic interactions, avoiding the use of harmful crosslinkers completely. Furthermore, natural polyelectrolytes - chitosan and alginate - were used. Upon mixing them, membranes were obtained by drying the PECs at 37ºC, yielding compact PECs without resorting to organicsolvents. The plasticizing effect of salt after synthesis was shown by measuring tensile mechanical properties, which were lower when samples were immersed in high ionic strength solutions.Salt was also used during membrane synthesis in different quan- tities (0 M, 0.15 M and 0.5 M in NaCl) yielding structures with no significant differences in morphology and degradation (around 15% after 3 months in lysozyme). However, swelling was higher (about 10x) when synthesized in the presence of salt. In vitro cell studies using L929 fibroblasts showed that cells adhered and proliferated preferentially in membranes fabricated in the presence of salt (i.e. the membranes with lower tensile strength). Structures with physical-chemical properties controlled with precision open a path to tissue engineering strategies depending on fine tuning mechanical properties and cellular adhesion simply by changing ionic strength during membrane manufacture